Irrigation to transform agriculture and food systems in Africa South of the Sahara - Ringler, Claudia; Mekonnen, Dawit Kelemework; Xie, Hua; Uhunamure, Agbonlahor Mure (International Food Policy Research Institute, 2020)
The contribution of irrigation to food security has been essential, and irrigated production currently accounts for 40 percent of global food production on less than a third of the world’s harvested land. Irrigation will be even more essential for future food production because of climate change and associated variability in water availability (Rosegrant, Ringler, and Zhu 2009; Ringler 2017). Irrigated agriculture supports food production in dry seasons and in areas that receive too little rainfall to grow food, and increasingly supplements production in areas with less-certain rainfall regimes. Irrigated yields are generally 30‒60 percent higher than yields of rainfed crops, as irrigation supports higher-yielding seeds and stimulates application of other inputs, such as fertilizers (Rosegrant, Ringler, and Zhu 2009). Irrigation accounts for approximately 70 percent of total global water withdrawals, including from groundwater, and for more than 80 percent of consumptive water use of withdrawn water (FAO 2016; Ringler 2017; WWAP 2019). Livestock watering and freshwater aquaculture are additional small, but growing agricultural water uses.